Analysis of Accounting Information System Design of Accounting Bookings Based On Microsoft Excel In Cv. Surya Anugerah Investindo - Yanna Eka Pratiwi; Buyung Cahya Perdana (Journal of Economy, Accounting and Management Science (JEAMS), 2020)
Seeing the importance of accounting information systems today for organizational progress in helping the implementation of accounting bookkeeping, so it requires a fast and accurate recording process. CV. Surya Anugerah Investindo is a developing company in the field of cobroke property, there is still no accounting information system so that making accounting books is still manual. The weaknesses are that the management or the data process is slow, requires a lot of effort or stages, the information generated has a high enough potential for error. The purpose of this study is to try to design and implement an accounting information system based on Microsoft Excel to produce accounting bookkeepers as needed. Data obtained directly from the company through interviews and documentation. Based on the data obtained, states that the accounting information system CV. Surya Anugerah Investindo has not implemented a computer-based accounting information system. From these weaknesses, researchers provide suggestions for the design of accounting books using a Microsoft Excel- based accounting information system.